Pendidikan Karakter Dalam Upaya Mengantisipasi Maraknya Seks Bebas Di Kalangan Pelajar SMA Sudirman Bruno Purworejo - Faridah, Ida (MADINAH, 2020)
This study aims to determine the role of character education in anticipating the prevalence of free sex among students at Sudirman Islamic Senior High School, Bruno Purworejo. This research method uses descriptive qualitative research methods. The research site is at Sudirman Bruno Islamic Senior High School, Purworejo. Data collection techniques used include: observation, interviews, documentation and data were analyzed by reducing the data and presenting data. The validity of the data was using triangulation by testing the understanding obtained in the interview and observation method. The results of the study concluded that the role of character education in anticipating the rise of free sex at Sudirman Bruno Purworejo Islamic High School was (1), forming religious students. (2), forming a good character can be trained through good deeds, for example being honest in tests. (3), forming an attitude of responsibility can be realized through scout extracurricular activities. (4), forming self-control that can be realized through Civics lessons on self-control material. After the implementation of character education, it was able to suppress free sex among students of Sudirman Islamic Senior High School.